GAPS-megacities: A new global platform for investigating persistent organic pollutants and chemicals of emerging concern in urban air. (December 2020) - Saini, Amandeep; Harner, Tom; Chinnadhurai, Sita; Schuster, Jasmin K.; Yates, Alan; Sweetman, Andrew; Aristizabal-Zuluaga, Beatriz H.; Jiménez, Begoña; Manzano, Carlos A.; Gaga, Eftade O.; Stevenson, Gavin; Falandysz, Jerzy; et al.
Abstract: A pilot study was initiated in 2018 under the Global Atmospheric Passive Sampling (GAPS) Network named GAPS-Megacities. This study included 20 megacities/major cities across the globe with the goal of better understanding and comparing ambient air levels of persistent organic pollutants and other chemicals of emerging concern, to which humans residing in large cities are exposed. The first results from the initial period of sampling are reported for 19 cities for several classes of flame retardants (FRs) including organophosphate esters (OPEs), polybrominated diphenyl ethers (PBDEs), and halogenated flame retardants (HFRs) including new flame retardants (NFRs), tetrabromobisphenol A (TBBPA) and hexabromocyclododecane (HBCDD). The two cities, New York (USA) and London (UK) stood out with ∼3.5 to 30 times higher total FR concentrations as compared to other major cities, with total concentrations of OPEs of 15, 100 and 14, 100 pg/m 3, respectively. Atmospheric concentrations of OPEs significantly dominated the FR profile at all sites, with total concentrations in air that were 2–5 orders of magnitude higher compared to other targeted chemical classes. A moderately strong and significant correlation (r = 0.625, p  < 0.001) was observed for Gross Domestic Product index of the cities with total OPEs levels. Although large differences in FR levels were observed between some cities, when averaged across the five United Nations regions, the FR classes were more evenly distributed and varied by less than a factor of five. Results for Toronto, which is a 'reference city' for this study, agreed well with a more in-depth investigation of the level of FRs over different seasons and across eight sites representing different urban source sectors (e.g. traffic, industrial, residential and background). Future sampling periods under this project will investigate trace metals and other contaminant classes, linkages to toxicology, non-targeted analysis, and eventually temporal trends. The study provides a unique urban platform for evaluating global exposome. Graphical abstract: Image 1 Highlights: A global initiative targeting 20 megacities/major cities to monitor POPs in urban air. Levels of OPEs, PBDEs, NFRs, HBCDD and TBBPA reported here from initial sampling. GDP of cities had significant positive correlation with the levels of OPEs. OPEs were 2–5 orders of magnitude higher than other FRs across the globe. Relatively even distribution of FRs, when averaged across the five United Nations' regions. Abstract : A global study across 20 megacities/major cities reporting urban air concentrations of flame retardants and plasticizers.